Establishing extracorporeal membrane oxygenation team increased number of patients and improved data recording - Komindr, Atthasit (J Intensive Care, 2019)
BACKGROUND: For patients treated with extracorporeal membrane oxygenation (ECMO), employing a well-coordinated, multidisciplinary team specializing in ECMO has reportedly been effective in delivering better clinical outcomes. This study aims to assess the impact of establishing such a specialized team for patients treated with ECMO. METHOD: This retrospective cohort study was performed at a tertiary-care hospital in Japan. We reviewed medical records of all consecutive patients treated with ECMO during October 2010–September 2016. The results obtained in pre-ECMO team cases (PRE group; October 2011–September 2012) and post-ECMO team cases (POST group; October 2014–September 2015) were compared. RESULTS: The results obtained in pre-ECMO team cases (PRE group; October 2011–September 2012) and post-ECMO team cases (POST group; October 2014–September 2015) were compared. During the study period, 177 patients were treated with ECMO. Before the introduction of ECMO team, an average of 22.7 patients underwent ECMO treatment per year; after establishing ECMO team, this number increased to 36.3 patients per year. ECMO was applied mainly to cardiac arrest patients 52/69 (75%). The PRE (n = 27) and POST (n = 42) groups did not differ with regard to the survival rate to hospital discharge, ECMO duration, ventilator days, and length of hospital stay. However, PaO(2) and positive end-expiratory pressure were significantly higher in the POST group at 6 h after ECMO initiation than those in the PRE group [367 (186–490) vs. 239 (113–430) mmHg, p = 0.047 and 8 (5–10) vs. 7 (5–8) cmH(2)O, p = 0.01, respectively]. In addition, data recording the detailed time points of ECMO initiation was conducted in significantly more cases in the POST group (28/126 (22%) than in the PRE group (6/81 (7%); p = 0.01). CONCLUSIONS: Following the establishment of an ECMO team, the survival rate of patients treated with ECMO, ECMO duration, and length of hospital stay were not improved. However, the number of ECMO cases increased and the recording of clinical data was improved.